Hubungan Lama Sakit, Tingkat Pendidikan, Motivasi Pasien, dan Dukungan Keluarga dengan Kepatuhan Diet Pasien Diabetes Melitus Tipe II di Rumah Sakit Daerah (RSD) Mangusada Kabupaten Badung Bali - Manutama, Putu Agi Abhimana; Arjita, I Putu Dedy; Saputra, I Putu Bayu Agus; Bagiansah, Mamang (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Diabetes mellitus is a non-infectious disease that has become one of the health threats worldwide. Dietary adherence has a very important function in the management of DM. factors that can affect the dietary adherence of DM patients, namely education, knowledge, motivation, family support, and length of suffering. To analyze the relationship of length of illness, education level, patient motivation, and family support with dietary compliance of Type II DM patients at RSD Mangusada Badung Regency Bali. Observational analytic quantitative research with simple random sampling research design with a sample size of 92 respondents. Data were analyzed by Chi-Square test and Spearman Rank test with a significance value limit (p-value) <0.05. The results showed that the majority of respondents were 51-60 years old 44 (47.8%), the majority of respondents were male 48 (52.2%), 78 (84.8%) complied with the diet, the length of illness without complications 42 (45.7%), higher education 35 (38%), good patient motivation 75 (81.5%), good family support 71 (77.2%). Bivariate analysis showed that there was a significant relationship between length of illness with dietary compliance (p=0.048), education level with dietary compliance (p=0.015), patient motivation with dietary compliance (p=0.001), and family support with dietary compliance (p=0.009). Length of illness, education level, patient motivation, and family support are associated with dietary adherence of Type II DM patients at Mangusada Hospital, Badung Regency, Bali. Keywords: Diabetes Melitus, Dietary Compliance, Long Illness, Level Of Education, Patient Motivation, Family Support  ABSTRAK Diabetes melitus merupakan penyakit non-infeksi yang menjadi salah satu ancaman kesehatan di seluruh dunia. Kepatuhan diet memiliki fungsi yang sangat penting dalam pengelolaan DM. faktor-faktor yang dapat mempengaruhi kepatuhan diet pasien DM, yaitu pendidikan, pengetahuan, motivasi, dukungan keluarga, dan lama menderita. Menganalisis hubungan lama sakit, tingkat pendidikan, motivasi pasien, dan dukungan keluarga dengan kepatuhan diet pasien DM Tipe II di RSD Mangusada Kabupaten Badung Bali. Penelitian kuantitatif analitik observasional dengan desain penelitian simple random sampling dengan besar sampel 92 responden. Data di analisis dengan uji Chi-Square dan uji Rank Spearman dengan batas nilai signifikansi (p-value) <0,05. Hasil penelitian menunjukkan mayoritas responden berusia 51-60 tahun 44 (47,8%), responden mayoritas berjenis kelamin laki-laki 48 (52,2%), patuh menjalani diet 78 (84,8%), lama sakit tanpa komplikasi 42 (45,7%), pendidikan tinggi 35 (38%), motivasi pasien baik 75 (81,5%), dukungan keluarga baik 71 (77,2%). Analisis bivariat menunjukkan terdapat hubungan yang signifikan antara lama sakit dengan kepatuhan diet (p=0,048), tingkat pendidikan dengan kepatuhan diet (p=0,015), motivasi pasien dengan kepatuhan diet (p=0,001), dan dukungan keluarga dengan kepatuhan diet (p=0,009). Lama sakit, tingkat pendidikan, motivasi pasien, dan dukungan keluarga berhubungan dengan kepatuhan diet pasien DM Tipe II di RSD Mangusada Kabupaten Badung Bali. Kata Kunci: Diabetes Melitus, Kepatuhan Diet, Lama Sakit, Tingkat Pendidikan, Motivasi Pasien, Dukungan Keluarga